COORDINATION ROLE OF THE IVANO-FRANKIVSK REGIONAL STATE ADMINISTRATION IN DECENTRALIZATION PROCESSES (Coordinates of Public Administration, 2026)
The article provides a comprehensive analysis of the transformation of the public administration system in Ukraine in the context of decentralization of power with an emphasis on the role of regional state administrations as subjects of regional governance. The historical evolution of decentralization processes from the dominance of the centralized administrative-command model to the modern paradigm of public administration focused on strategic coordination, partnership and effectiveness is revealed. Scientific approaches to the interpretation of decentralization as a multidimensional category combining legal, institutional, financial and managerial dimensions are summarized, and the change in the functional purpose of regional state administrations from administrative-control to coordination-strategic is justified. Using the example of the Ivano-Frankivsk region, the features of the implementation of the decentralization reform are analyzed, in particular, the formation of a new administrative-territorial basis, the development of a network of territorial communities, the transformation of the powers and financial capacity of local self-government. The specifics of the region are outlined, related to the mountainous nature of the territories, the asymmetry of the socio-economic development of communities and the impact of martial law on management priorities. The results of decentralization are analyzed from the standpoint of institutional, financial and managerial efficiency, positive effects and problematic aspects of the implementation of the reform at the community level are identified. The need for further strengthening the coordination, analytical and service-support role of the regional state administration in interaction with territorial communities, as well as the development of a system for monitoring and evaluating the effectiveness of decentralization processes as a condition for sustainable regional development is substantiated.